Analisis Pengaruh Financial Deepening Terhadap Pertumbuhan Ekonomi Indonesia - Cahaya Anis Kamila; Tiara Nirmala (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effects financial deepening on Indonesia's economic growth in the long and short run for the period 2014Q1-2024Q4. The analytical method used is the Autoregressive Distributed Lag (ARDL) with an Error Correction Model (ECM) approach. The independent variables include the broad money supply ratio (M2), private sector credit ratio (CPS), and stock market capitalization ratio (SMC), with the foreign direct investment ratio (FDI) as a control variable, and real GDP gworth as dependant variable. The results show that In the long run, M2 and CPS have a significant negative effect on economic growth, while SMC has a positive but insignificant effect. In the short run, M2 in the current period has a significant negative effect, but reverses to a significant positive effect two periods prior. CPS in the current period is not significant, but shows a significant positive effect one period prior. SMC is only significant and positive at one lag period.